Ethnobotanical Study of Plants Used by People in Hiang Indigenous Forest Kerinci, Jambi - Andesmora, Evan Vria; Muhadiono, Muhadiono; Hilwan, Iwan (Journal of Tropical Life Science, 2017)
Indonesia is a high-abundance tropical forests country. It plays a very important role for world life because of its species richness than others. One of the forest resources in Indonesia is indigenous forests. Indonesia is rich of local wisdom such as that possessed by indigenous peoples. Indigenous peoples have a potential of the biological resources conservation. As a sustainable management tradition, communities around indigenous forest also have the efforts to preserve the forest.  The data collection of community knowledge about plants was conducted by interviews and direct-field observation. Data were analyzed using index of cultural significance. The results showed that there are 48 species of plants utilized by communities in Hiang Indigenous Forest, 27 species are used as firewoods, 15 species as building materials, 7 species as medicinal plants, 6 species as traditional handicraft ingredients and 4 species as secondary foods and traditional ritual materials. Most of widely-used plants by the community are Altingia excels, and Styrax benzoin is used as incense in a traditional ritual.